REVIEW ARTIKEL AKTIVITAS ANTIBAKTERI EKSTRAK RIMPANG KUNYIT (Curcuma domestica Val) TERHADAP BEBERAPA SAMPEL BAKTERI - Sheila Meitania Utami; Diah Permata Sari; Nurwulan Adi Ismaya; Erwin Herdiawan (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2022)
The increase in antibiotic resistance is very fast throughout the world, this is a problem because it threatens human health globally. The increase in antibiotic resistance is due to overprescribing of antibiotics, as well as poor infection prevention and control. The use of traditional medicine can be used as an alternative treatment in overcoming health problems, prevention, and healing. Traditional medicine is considered safer than synthetic medicine, one of the plants that has antibacterial benefits is turmeric rhizome (Curcuma domestica Val). Turmeric rhizome has an antibacterial effect against gram negative and gram positive bacteria. This study aims to determine the antibacterial activity and active compounds contained in turmeric rhizome extract that can produce an antibacterial effect. The type of research used is descriptive using the Literature Review method by collecting various sources from 8 research journals that have been published and come from the internet. Turmeric rhizome extract is known to contain curcumin, alkaloids, flavonoids, essential oils, phenols, saponins, tannins, and terpenoids compounds that have antibacterial properties. The results of the literature review of the antibacterial activity test of turmeric rhizome extract showed that the antibacterial activity was classified as moderate to very strong against Escherichia coli (9 mm), Pseudomonas aeroginosa (7,8 mm), Bacillus cereus (11,1 mm), Salmonella typhi (12.1 mm), Staphylococcus aereus (10 mm), and Propionibacterium acnes (20.8 mm), while Bacillus subtilis (1.03 mm) was classified as weak.